Left Atrial Appendage Occlusion: British Cardiovascular Intervention Society and British Heart Rhythm Society Position Statement - Tim R Betts; Patrick A Calvert; Lee N Graham; Gerald J Clesham; Ashan Gunarathne; Brian Clapp; Dhiraj Gupta; Jan Kovac; James D Newton; David Hildick-Smith (Arrhythmia & Electrophysiology Review)
Percutaneous left atrial appendage occlusion aims to reduce the risk of stroke in patients with AF, particularly those who are not good candidates for systemic anticoagulation. The procedure has been studied in large international randomised trials and registries and was approved by the National Institute for Health and Care Excellence in 2014 and by NHS England in 2018. This position statement summarises the evidence for left atrial appendage occlusion and presents the current indications. The options and consensus on best practice for pre-procedure planning, undertaking a safe and effective implant and appropriate post-procedure management and follow-up are described. Standards regarding procedure volume for implant centres and physicians, the role of multidisciplinary teams and audits are highlighted.